2017
DOI: 10.1002/mds.27022
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Deep Brain Stimulation for Movement Disorders: The Long Road to Clinical Therapy

Abstract: Continuous high-frequency DBS is an established treatment for essential tremor and Parkinson’s disease. Current developments focus on trying to widen the therapeutic window of DBS. Adaptive DBS (aDBS), where stimulation is dynamically controlled by feedback from biomarkers of pathological brain circuit activity, is one such development. Relevant biomarkers may be central, such as local field potential activity, or peripheral, such as inertial tremor data. Moreover, stimulation may be directed by the amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
164
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 183 publications
(168 citation statements)
references
References 75 publications
1
164
0
Order By: Relevance
“…However, there are several reasons why adaptive DBS could improve this therapy. Reduction in stimulation current without loss of therapeutic benefit has the potential to reduce stimulation-induced adverse effects 19 , as well as prolong battery life or allow greater miniaturization of the relatively large pulse generators now in use 20 . Further, some of the PD patients most in need of DBS are also among the most difficult to successfully program: those who alternate between extreme states of dyskinesia and bradykinesia with little in-between time (“brittle fluctuators”) 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several reasons why adaptive DBS could improve this therapy. Reduction in stimulation current without loss of therapeutic benefit has the potential to reduce stimulation-induced adverse effects 19 , as well as prolong battery life or allow greater miniaturization of the relatively large pulse generators now in use 20 . Further, some of the PD patients most in need of DBS are also among the most difficult to successfully program: those who alternate between extreme states of dyskinesia and bradykinesia with little in-between time (“brittle fluctuators”) 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies were not included because they did not meet inclusion criteria or have been reported since we concluded the review process. Examples are the assessment of interventions administered on an as‐needed regimen, including the more recently studied octanol and its derivatives, open label assessment of perampanel, customized approach for botulinum toxin administration to improve safety in the treatment of hand tremor, other DBS approaches with assessment of targets such as the Zona Incerta/Posterior Subthalamic area, the STN, use of constant‐current or closed loop stimulation paradigms, and novel MRI‐guided approaches for thalamotomy . These interventions will likely merit assessment in a future MDS‐EBM review on ET.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the relationship with tremor is debated. Although other STN‐LFP signals like theta‐band (3‐8 Hz) activity show promise in relation to tremor, additional input signals to monitor tremor might be needed . Third, the clinical relevance or symptomatic contribution of high‐ versus low‐beta bands is a topic of discussion .…”
Section: Adbs Based On Electrophysiological Recordingsmentioning
confidence: 99%
“…First, a ramping onset, which increases the stimulation voltage from zero toward a predefined amplitude, can be used to overcome paresthesia . Furthermore, ON/OFF AM can be applied in a phase‐dependent manner, in which a stimulus is applied with a fixed latency to an input signal . Phase‐dependent aDBS is hypothesized to have advantages over standard aDBS.…”
Section: Stimulation Parameter Modulation In Adbsmentioning
confidence: 99%
See 1 more Smart Citation